English as an Additional Language (EAL) SoW - Jester, Caroline; Stoneman, Claire (Playwriting Across the Curriculum, 2012)
This SoW is primarily written for students newly-arrived to the UK, who speak English as an additional language (EAL). The SoW can also be adapted for use with students who are not newly-arrived but still speak English as an additional language. Newly-arrived students on induction programmes can write a play together, or this can work with a mixed-ability group: newly-arrived students and students who have gone into the mainstream classes and have more advanced English. There is no limit to the number of first languages that can work together; the SOW is designed to incorporate multiple voices and cultures through its narrative. The play will be shaped by the individual experiences of the students. These lessons have been designed to last longer than the average 70-minute lesson, and we suggest two hours because the students may need extra time to understand and develop their ideas through the activities. We have found this immersion time to be more effective and less disjointed for EAL learners.